Analisis Kualitas Gambar Antara Rekonstruksi Dan Reformat MSCT Thorax Pada Kasus Tumor Paru - Alfian Yusuf Al Rasyid; Yeti Kartikasari; Dartini Dartini (Jurnal Imejing Diagnostik (JImeD), 2015)
Backgroud: A CT Scan of thorax on tumor case is used to obtain information about the image quality on axial part of thorax and to determine the types of lesion. In the process, there were two techniques that often used. The techniques used was reconstruction technique and reformat technique. Reconstruction technique and reformat technique have a difference in the process of producing an image. This study aims to tell the image quality between MSCT thorax reconstruction and reformat on axial part of thorax on lung tumor case and to know which image quality better between MSCT thorax reconstruction and reformat on axial part of thorax on lung tumor case.Methods: The study was quantitative descriptive research. Subjects of this research was three patients. Image quality assessed by three radiology physician using reconstruction and reformat technique. Data was analyzed by statistical test using wilcoxon test. Ho was received when ≥ 0,05. It means that there were differences of image quality between MSCT thorax reconstruction and reformat on lung tumor case.Results: The results of the research based on statistical test were there was the difference of MSCT thorax between reconstruction and reformat on lung tumor case with the result of Wilcoxon test was 0,001 (p0.05). The test results mean rank value of reconstruction was 18,7 and mean rank value of reformat was 14,93.Conclusion: Based on this assessment, so reconstruction method was choosen as standard operational procedure for examination.